Kue kering dengan subtitusi tepung kulit singkong dan tepung labu kuning sebagai jajanan anak sekolah - Asmaruddin Pakhri2; Meliani Meliani; Sitti Saharia Rowa (Jurusan Gizi Poltekkes Kemenkes Makassar, 2019)
Urban or rural communities can not be separated from snacks along with the limited time to process their own food. The advantages of snacks are easy to get, taste good. One of the type of biscuit is cookies or pastries. To find out the acceptability of pastries with substitution of cassava skin flour and pumpkin flour as a snack for elementary school children. This type of research is experimental. Acceptability was assessed based on a hedonic test of 30 untrained panelists. Analysis of the acceptability test data using the Kruskal Wallis H Test with the SPSS program. Then presented in the form of tables and narratives. The results of the study showed that the acceptability of food was cookies with substitution of cassava skin flour and pumpkin flour which was most preferred by the panelists, namely on F5. In the aspect of color and aroma of panelists like as much as 93%, the texture aspect of panelists likes as much as 97% while in the aspect of taste panelists like as much as 100%. This is because it is influenced by the substitution of cassava skin flour and pumpkin flour which is given differently. Statistical test results show that there is a difference in the acceptability of pastries in terms of aroma criteria with and in terms of taste criteria. So the conclusion of the acceptability of pastries with the substitution of cassava skin flour and pumpkin flour as a snack for elementary school students in terms of aspects of color, aroma, texture and taste, namely in Formula 5 or called a concentration of 25% cassava skin flour and pumpkin flour